Pathogenesis of Type - 2 Diabetes Mellitus - Alagh, Arzoo; Shukla, Samarth (A Concise Clinicopathological Handbook of Diabetes Mellitus, 2021)
Amongst the diabetes, Type 2 Diabetes Mellitus is the most common type and comprises of over 90% of the cases. It is characterized by 2 metabolic defects, viz, 1) Deranged insulin secretion and 2) Insulin resistance. The insulin resistance syndrome i.e Metabolic syndrome is characterized by 5 factors amongst which one is impaired glucose tolerance and impaired fasting glucose. Obesity, sedentary lifestyle, high caloric diet are the main culprits to increase the incidence and prevalence of diabetes.